Joint attention at 10 months of age in infant–mother dyads: contrasting free toy-play with semi-structured toy-play - Mateus, Vera (2013)
Fifty-two 10-month-olds and their mothers were observed in free toy-play and semi-structured toy-play for assessing joint attention capabilities. Mothers exhibited more bids for joint attention during semi-structured toy-play. Infants' response to maternal behaviors and their bids for initiating joint attention were higher during free toy-play.